Pengaruh Teknologi dan Motivasi Kerja terhadap Produktivitas Petani Cengkeh di Desa Munduk Kecamatan Banjar Kabupaten Buleleng - Herawati, Ni Kadek Sabrina; I Putu Arya Dharmayasa (Jurnal Pendidikan Ekonomi Undiksha, 2025)
The purpose of this study was to determine (1) the effect of technology on the productivity of clove farmers in Desa Munduk Kecamatan Banjar Kabupaten Buleleng, (2) the effect of work motivation on the productivity of clove farmers in Desa Munduk Kecamatan Banjar Kabupaten Buleleng, (3) the effect of technology and work motivation on the productivity of clove farmers in Desa Munduk Kecamatan Banjar Kabupaten Buleleng. The population in this study were clove farmers in Desa Munduk Kecamatan Banjar Kabupaten Buleleng, especially land owners totaling 564 farmers. The sampling technique with a sample size of 122 farmers. The data collection method used a questionnaire and was analyzed using multiple liniear regression analysis. The result of the study showed that (1) there was a positive and significant effect of technology on the productivity of clove farmers partially, (2) there was a positive and significant effect of work motivation on the productivity of clove farmers partially, (3) technology and work motivation simultaneously had a positive and significant effect on the productivity of clove farmers.